Industrialization and Consumption of Fossil Energy are the Main Determinants of Environmental Degradation in Water Catchment Areas in Indonesia - Sasana, Hadi; Prasetyanto, Panji Kusuma; Priyono, Nuwun (International Journal of Energy Economics and Policy, 2022)
Economic growth is the main goal of the global economy. However, increasing economic growth often results in increased CO2 emissions and encourages environmental degradation. This study analyzes the impact of industrialization, consumption of fossil energy, economic growth, and population activities on CO2 emissions in upland water catchment areas. Data analysis using panel data regression, in a span of 20 years. The results of the study show that economic factors, namely industrialization and consumption of fossil energy, are the main determinants of increasing CO2 emissions. Meanwhile, social aspects such as education, waste generation, and population have no effect on CO2 emissions.